Endoscopic Submucosal Dissection Versus Surgery for Superficial Esophageal Squamous Cell Carcinoma: A Propensity Score-Matched Survival Analysis. Issue 7 (13th July 2020) - Lee, Hyun Deok; Chung, Hyunsoo; Kwak, Yoonjin; Choi, Jinju; Lee, Ayoung; Kim, Jue Lie; Cho, Soo-Jeong; Kim, Sang Gyun
Abstract : INTRODUCTION: Endoscopic submucosal dissection (ESD) is a preferred treatment option for superficial esophageal squamous cell carcinoma (SESCC). However, only few studies compared long-term survival outcomes of ESD with surgery. This study compared the overall survival (OS), recurrence-free survival, and complication rates of ESD with those of surgery. METHODS: We reviewed patients who underwent ESD (n = 70) or surgery (n = 114) for SESCC at Seoul National University Hospital from 2011 to 2017. A propensity score-matched analysis was used to reduce selection bias. To increase the precision of our results interpretation, subgroups were analyzed according to the depth of tumor invasion. RESULTS: In the matching study, the ESD group (n = 34) showed comparable survival outcomes with the surgery group (n = 34). The 5-year OS rates were 89.4% vs 87.8% for the ESD and the surgery groups, respectively; similarly, the 5-year recurrence-free survival rates were 90.9% and 91.6%, respectively. The ESD group showed a lower early major complication rate (2.9% [1 of 34] vs 23.5% [8 of 34], P < 0.001) and shorter hospital stay (median, 3.0 days vs 16.5 days, P < 0.001) than the surgery group. In the tumor in situ (Tis)-subgroup, ESD showed better OS than esophagectomy ( P = 0.030). Between-group comparisons of survival outcomes in the T1a and T1b subgroups revealed no significant differences. DISCUSSION: Long-term outcomes of ESD are comparable with surgery for patients with SESCC. For early major complications and duration of hospital stay, ESD was associated with better outcomes than radical surgery. These results support ESD as the preferred treatment option for SESCC.